Entrepreneurial Activities in Postsecondary Education - Michael, Steve O.; Holdaway, Edward A. (Canadian Journal of Higher Education, 1992)
Postsecondary education in western countries has experienced four major phases in this century. An elite phase persisted until about 1945 when a reconstructionist phase emerged, reflecting a more democratic approach. The third phase of reductions in funding and support characterized the 1980s. Inadequate revenues to meet rising costs, government measures, and institutional efforts to become more market-oriented can be viewed as complementary developments which were largely responsible for the current entrepreneurial phase. Entrepreneurial aspects of postsecondary education include the extent to which users should pay, the balance between market-related and purely academic activities, the relative emphases upon basic and applied research, fundraising, and greater involvement of institutions and individuals in obtaining patents, licences, and cooperating with sizeable companies. A more entrepreneurial emphasis has implications for postsecondary administrators, especially in the matters of budget allocations, the need for more training of administrators, and increased attention to student needs. While a greater market orientation is warranted, care must be exercised to ensure that the academic mandate remains paramount.